Claudia Román. Prensa, política y cultura visual. El Mosquito (Buenos Aires, 1863-1893). Buenos Aires: Ampersand, 2017 - Míguez, Gustavo Ignacio (2018)
Fil: Fil: Míguez, Gustavo Ignacio. Universidad Nacional de Tres de Febrero; Argentina.